2023
DOI: 10.3390/ijms241310431
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Landscape during Ripening of Solid Endosperm from Two Different Coconut Cultivars Reveals Contrasting Carbohydrate and Fatty Acid Metabolic Pathway Modulation

Abstract: Cocos nucifera L. is a crop grown in the humid tropics. It is grouped into two classes of varieties: dwarf and tall; regardless of the variety, the endosperm of the coconut accumulates carbohydrates in the early stages of maturation and fatty acids in the later stages, although the biochemical factors that determine such behavior remain unknown. We used tandem mass tagging with synchronous precursor selection (TMT-SPS-MS3) to analyze the proteomes of solid endosperms from Yucatan green dwarf (YGD) and Mexican … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 86 publications
1
2
0
Order By: Relevance
“…The metabolome of the Yucatan green dwarf coconut is highly conserved with metabolomes reported for COD and MYD dwarf varieties from India, with respect to sugars, organic acids, and amino acid accumulation [4], and is consistent with the recently reported proteomics study for green dwarf coconut [49], although some discrepancies were also noted.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The metabolome of the Yucatan green dwarf coconut is highly conserved with metabolomes reported for COD and MYD dwarf varieties from India, with respect to sugars, organic acids, and amino acid accumulation [4], and is consistent with the recently reported proteomics study for green dwarf coconut [49], although some discrepancies were also noted.…”
Section: Discussionsupporting
confidence: 88%
“…A key enzyme in the glyoxylate cycle is isocitrate lyase (ICL), which catalyzes the cleavage of isocitrate into glyoxylate and succinate; succinate enters the mitochondria for subsequent reactions [57]. Félix et al [49] recently demonstrated that glyoxylate is significantly regulated during the ripening of coconut fruits, following an inverted bell curve, in agreement with the regulation of glycolysis. Glyoxylate and dicarboxylate metabolisms are also related to abiotic stress, providing a balance in metabolic changes to improve tolerance to drought stress [37].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation